2006
DOI: 10.1021/ja0573357
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processable Organic Field-Effect Transistors Utilizing an α,α‘-Dihexylpentathiophene-Based Swivel Cruciform

Abstract: A pentathiophene-based swivel cruciform, which allows rotation between the cruciform arms, was synthesized. Homogeneous microcrystalline films were processed from solution, and field-effect transistors utilizing this dimer gave hole mobilities up to 0.012 cm2/V.s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 33 publications
3
77
0
Order By: Relevance
“…[59] Various examples of extended conjugated systems with tetrahedral geometry have been developed in recent years. [60][61][62][63][64][65][66] Wilson and Griffin first reported tetrahedral molecules with oligo-p-phenylene arms (40). [60] Bazan and co-workers have developed various series of tetrahedral conjugated systems containing oligo(phenylenevinylenes) attached on tetraphenylmethane (41), tetraphenylsilane, or tetraphenyladamantane cores.…”
Section: D Conjugated Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…[59] Various examples of extended conjugated systems with tetrahedral geometry have been developed in recent years. [60][61][62][63][64][65][66] Wilson and Griffin first reported tetrahedral molecules with oligo-p-phenylene arms (40). [60] Bazan and co-workers have developed various series of tetrahedral conjugated systems containing oligo(phenylenevinylenes) attached on tetraphenylmethane (41), tetraphenylsilane, or tetraphenyladamantane cores.…”
Section: D Conjugated Systemsmentioning
confidence: 99%
“…Thus, Scherf and co-workers have synthesized cruciform nTs involving two quinquethiophene chains connected by a b-position of the median thiophene unit (47). [66] Electrochemical and optical data indicate weak interactions between the conjugated branches in the ground state. Differential scanning calorimetry (DSC) measurements did not reveal any glass transition, whereas X-ray diffraction data revealed that the films cast from chloroform solutions were polycrystalline.…”
Section: D Conjugated Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, functionalized, cruciform-shaped, conjugated fluorophores are well-known because they exhibit interesting optoelectronic properties due to their special, multi-conjugated-pathway structures. Examples of cruciform-shaped phores are the 1,2,4,5-tetrasubstituted(phenylethynyl) benzenes of Haley et al (Marsden et al, 2005), the X-shaped 1,2,4,5-tetravinyl-benzenes of Marks et al , the 1,4-bis(arylethynyl)-2,5-distyrylbenzenes of Bunz et al (Wilson  Bunz, 2005), and other cross-shaped fluorophores developed by Nuckolls et al (Miao et al, 2006) and Scherf et al (Zen et al, 2006). Therefore, their seminal studies on the structure-property relationships for those materials provided valuable information for the molecular design of material as model systems or promising candidates toward highperformance optoelectronic devices.…”
Section: Pyrene-based Cruciform-shaped -Conjugated Blue Light-emittimentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51] Materials with long alkyl chains, especially, have shown drastic morphological change after the thermal treatment, which lead to large change in the performance of TFT. [29][30][31]37,[42][43][44][45] Attached long alkyl chains added highly mobile nature to the molecular backbone, and this highly mobile nature makes it possible to change the film morphology greatly with a thermal treatment at a rather low temperature.…”
Section: -39mentioning
confidence: 99%